Evaluation of in vitro Cytotoxic and Anticancer Activities of Selected Plant Extracts Growing in Bangladesh - Suchana, Lutfunnahar; Rahman, M Oliur; Rashid, Mohammad A; Sultan, Md Zakir; Hassan, Md Abul (Dhaka University Journal of Pharmaceutical Sciences, 2024)
Abstract not available Dhaka Univ. J. Pharm. Sci. 23(2): 201-204, 2024 (December)